Relevance of barriers and facilitators in the use of health technology assessment in Colombia. (4th May 2018) - Dams, Florian; Gonzalez Rodriguez, Javier Leonardo; Cheung, Kei Long; Wijnen, Ben F. M.; Hiligsmann, Mickaël
Abstract: Objectives: Several studies, mostly from developed countries, have identified barriers and facilitators with regard to the uptake of health technology assessment (HTA). This study elicited, using best-worst scaling (BWS), what HTA experts in Colombia consider to be the most important barriers and facilitators in the use of HTA, and makes a comparison to results from the Netherlands. Methods: Two object case surveys (one for barriers, one for facilitators) were conducted among 18 experts (policymakers, health professionals, PhD students, senior HTA-researchers) from Colombia. Seven respondents were employees of the national HTA agency Instituto de Evaluación Tecnológica de Salud (IETS). In total, 22 barriers and 19 facilitators were included. In each choice task, participants were asked to choose the most and least important barrier/facilitator from a set of five. Hierarchical Bayes modeling was used to compute the mean relative importance scores (RIS) for each factor, and a subgroup analysis was conducted to assess differences between IETS and non-IETS respondents. The final ranking was further compared to the results from a similar study conducted in the Netherlands. Results: The three most important barriers (RIS >6.00) were "Inadequate presentation format", "Absence of policy networks", and "Insufficient legal support". The six most important facilitators (RIS >6.00) were "Appropriate timing", "Clear presentation format", "Improving longstanding relation", "Appropriate incentives", "Sufficient qualified human resources", and "Availability to relevant HTA research". The perceived relevance of the barriers and facilitators differed slightly between IETS and non-IETS employees, while the differences between the rankings in Colombia and the Netherlands were substantial. Conclusion: The study suggests that barriers and facilitators related to technical aspects of processing HTA reports and to the contact and interaction between researchers and policymakers had the greatest importance in Colombia.